Radiation diagnostics of injuries and complications with a blind penetrating wound of the chest received from a construction and installation gun - I. E. Popova; L. T. Khamidova; I. E. Goncharova; V. M. Abuchin; R. Sh. Muslimov; T. G. Barmina; E. A. Tarabrin; I. E. Selina; M. K. Nanoyan; O. A. Chernysheva (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2022)
On the example of a clinical case, the possibilities of radiation diagnosis of a rare type of injury received from a construction and installation gun are shown. The modern possibilities of radiation diagnostics in the detection of injuries and complications in a gunshot wound of the chest are shown. Ultrasound data on the presence of intrapleural contents allowed us to determine the penetrating nature of the wound. The data obtained by polypositional chest radiography gave an idea of the localization and size of the foreign body. During chest CT, an accurate anatomical characteristic of the wound canal was given, the exact localization of the foreign body was indicated, an intrapulmonary hematoma, a lung contusion were identified, the exact nature and volume of the intrapleural contents were determined. In the postoperative period, CT revealed PE and infarct pneumonia, and scintigraphy assessed the total deficit of lung perfusion, which affected the treatment tactics. In the diagnosis of complications of breast injury such as intrapulmonary hematoma, infarction pneumonia, inflammatory changes in the soft tissues of the chest wall, ultrasound diagnostic data are comparable with CT results.